CURRICULAR INTEGRATION AND EDUCATION FOR THE FUTURE - A POSSIBLE SOLUTION - Daniela Jeder; Daniela Jeder (Association of Social and Educational Innovation, 2020)
How can the school ensure the success of its students, how does it prepare them for a world that is constantly changing? What values, attitudes, what knowledge, skills do they form to really support them in facing these challenges? Teachers acknowledge that it is also a challenge for them. This paper supports the idea that curriculum integration is a potential solution, because it supports a quality education, which focuses on training student's skills for the 21st century - flexible, creative thinking, critical thinking, cooperation and communication, but also character formation, of the civic spirit.